Portfolio Assessment for the Teaching and Learning of Writing - Lam, Ricky (SpringerBriefs in Education,, 2018)
This book provides teachers, instructors, scholars, and administrators with a practical guide to implement portfolio assessment of writing in their work contexts. Unlike most existing volumes, which underscore theory building, it describes and discusses several key issues concerning how portfolio assessment can be carried out in authentic classrooms with a focus on its processes, reflective components, task types and design, scoring methods and actionable recommendations.